(untitled) (Journal of Educational and Psychological Sciences, 2019)
This study aimed to explore the reality of applying administrative reengineering in Imam Mohamed Bin Saud Islamic University from academic department heads point of view. To achieve this goal, a sample of departments’ heads and agents consisting of 61 individuals. A Reengineering questionnaire, prepared by the researcher was applied. The questionnaire has three dimensions which are: electronic jobs, financial resources management and professional development of departments’ heads. The researcher used the descriptive analytic approach. Conclusions of the study were as follow: The study population agreed on the availability of technological tools , the quality of services applying the performance incentives , simplifying work procedures, applying problem solving and decision making. The rate of agreement on these dimensions was (4.006)The study population agrees strongly on applying working with others and through them in Imam Mohamed Ibn Saud University. The rate of agreement on the dimensions (3072). The study sample moderately agrees that there are difficulties in applying Reengineering Management at the University of Imam Muhammad bin Saud Islamic University. Their approval rates (3037).